2011
DOI: 10.1590/s1806-37132011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da acurácia de preditores de mortalidade na pneumonia associada à ventilação mecânica

Abstract: Objective: Levels of procalcitonin, midregional pro-atrial natriuretic peptide (MR-proANP), C-terminal provasopressin (copeptin), and C-reactive protein (CRP), as well as Sequential Organ Failure Assessment (SOFA) scores, are associated with severity and described as predictors of outcome in ventilator-associated pneumonia (VAP). This study sought to compare the predictive value of these biomarkers for mortality in VAP. Methods: An observational study of 71 patients with VAP. Levels of procalcitonin, MR-proANP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…3). The authors concluded that the increase of serum procalcitonin is an important diagnostic marker in identifying and predicting the outcome of VAP, and its usefulness is confirmed by the result of many other studies (23, 24, 25). …”
Section: Diagnostic Importance Of Procalcitoninmentioning
confidence: 78%
“…3). The authors concluded that the increase of serum procalcitonin is an important diagnostic marker in identifying and predicting the outcome of VAP, and its usefulness is confirmed by the result of many other studies (23, 24, 25). …”
Section: Diagnostic Importance Of Procalcitoninmentioning
confidence: 78%
“…The V1a receptor is widely expressed and mediates AVPs prothrombotic and vasoconstrictor effects. Thus, AVP agonists are used in treating bleeding and hypotensive disorders (1517). Through V1a receptor AVP also mediates liver glycogenolysis (16,17).…”
Section: Function Of Avpmentioning
confidence: 99%
“…Through V1a receptor AVP also mediates liver glycogenolysis (16,17). The V1b receptor is expressed in the pituitary gland and pancreas (15,16). Through this receptor AVP stimulates the release of adrenocorticotropic hormone.…”
Section: Function Of Avpmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important sub-area in our field in which there has been an increase in interest and in scientific production is intensive care, ( 32 - 34 ) including mechanical ventilation and the essential participation of respiratory therapy, an area in which the volume of research has also increased. ( 35 , 36 ) The use of ventilatory support and extracorporeal membrane oxygenation was the subject of a study conducted in the city of São Paulo ( 37 ) and of an editorial authored by Professor Alan Morris of Salt Lake City, Utah.…”
mentioning
confidence: 99%